Challenging case of horseshoe kidney double fracture - Cortese, Francesco (Int J Surg Case Rep, 2017)
INTRODUCTION: Renal injuries occur in 10% of blunt abdominal traumas, 7% of these occur in kidneys with congenital or acquired disorders. Trauma of horseshoe kidney is an uncommon finding. PRESENTATION OF A CASE: We present the case of 31 year-old caucasian man with no remarkable personal records, who was brought to our Trauma Unit soon after being involved in a motorcycle collision. A Contrast Enhanced – Multi Detector Computed Tomography (ce-MDCT) revealed a double disconnection of a horseshoe kidney. The patient was not aware of bearing such abnormality. DISCUSSION: Trauma of horseshoe kidney is an uncommon finding. The abdominal ce-MDCT scan is the diagnostic tool of choice since the renal anatomy, injury grading and vascular or urinary tract abnormalities are well depicted and easily identified. The conservative management of these injuries is associated with a lower rate of nephrectomies and kidney failure while selective trans-catheter renal embolization is a challenging treatment option. However surgery can be a treatment of choice and should be aimed to preserve renal function. Conclusion: the interest in our case lies in the rarity and particular anatomical aspect of such injuries and the implication related to its management in an emergency setting.